2009
DOI: 10.1080/14616690802248042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Divorce on Children's Educational Attainment in a Mediterranean and Catholic Society

Abstract: Previous research has found parental divorce to have negative effects on children's educational attainment; in addition, it has been noted that the effects of divorce are not the same in all western societies. However, research on Catholic and southern European countries is missing. The aim of this paper is to add to the research on the relation between parental divorce and the educational attainment of children in Catholic and southern European societies. Italian society differs from other western societies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
4
40
1
2
Order By: Relevance
“…Some studies have shown that children from disadvantaged families suffer more from divorce than children from affluent families (Albertini & Dronkers, 2009;Grätz, 2015;Mandemakers & Kalmijn, 2014). This evidence is consistent with the notion of "diverging destinies."…”
Section: Introductionsupporting
confidence: 64%
“…Some studies have shown that children from disadvantaged families suffer more from divorce than children from affluent families (Albertini & Dronkers, 2009;Grätz, 2015;Mandemakers & Kalmijn, 2014). This evidence is consistent with the notion of "diverging destinies."…”
Section: Introductionsupporting
confidence: 64%
“…In recent years, researchers have become increasingly interested in how the effects of parental separation on child outcomes vary with social background (Albertini and Dronkers 2009; Augustine 2014; Bernardi and Boertien 2016; Bernardi and Radl 2014; Biblarz and Raferty 1993, 1999; Biblarz et al 1997; Cavanagh and Huston 2006; Elliott and Richards 1991; Fischer 2007; Jonsson and Gähler 1997; Mandemakers and Kalmijn 2014; Martin 2012; McLanahan and Sandefur 1994). From a theoretical perspective, it is unclear whether one should expect the negative consequences of parental separation on child outcomes to be greater or smaller for socio-economically advantaged children.…”
mentioning
confidence: 99%
“…Despite several papers addressing the empirical question of whether children from distinct social backgrounds experience different ‘separation penalties’, no clear answer can yet be given. Some studies conclude that greater adverse effects are observed in children from higher socio-economic backgrounds (Bernardi and Radl 2014; Biblarz and Raferty 1993; Martin 2012; McLanahan and Sandefur 1994), whereas others come to the opposite conclusion (Albertini and Dronkers 2009; Augustine 2014; Cavanagh and Huston 2006; Grätz 2015; Mandemakers and Kalmijn 2014). …”
mentioning
confidence: 99%
“…For instance, Grätz (2015) provided one of the few results on Germany, and found that only the school performance of socioeconomically disadvantaged children is affected by parental separation. Studies on Italy, the Netherlands, and Sweden find smaller effects for children with resourceful mothers (Albertini and Dronkers 2009;Fischer 2007;Jonsson and Gähler 1997), but larger effects for children with resourceful fathers (Fischer 2007;Jonsson and Gähler 1997). Single-country studies on the United Kingdom and the United States in general support the conclusion that socioeconomically advantaged children are affected more by separation (Biblarz and Raftery 1993;Mandemakers and Kalmijn 2014;Martin 2012;McLanahan and Sandefur 1994).…”
Section: Family Structure and Socioeconomic Inequality 171mentioning
confidence: 96%
“…First, substantial research shows that children's educational attainment suffers less from parental divorce if they have more highly educated mothers (Albertini and Dronkers 2009;Fischer 2007;Grätz 2015). However, the two studies that used test scores rather than educational attainment obtained contradictory results.…”
Section: Previous Research and Limitationsmentioning
confidence: 99%